Isolating membrane and preparation method thereof, battery and electric device

CN119585937APending Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380055500.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In lithium-ion batteries, the phenomenon of lithium precipitation in the negative electrode leads to the growth of lithium dendrites, destroys the solid electrolyte interface film, and reduces battery cycle performance. Traditional improvement methods have reached a bottleneck and it is difficult to further improve battery performance.

Method used

Design an isolation film, including a doped graphene oxide modified layer. The electronegativity of the doped atoms is ≥ 2. It is used in secondary batteries to regulate the transmission and deposition of lithium ions and reduce the degree of lithium evolution. It uses hot pressing and drying. Method to prepare the isolation film.

Benefits of technology

By regulating the deposition and transmission of lithium ions, the uniformity of deposition on the negative electrode surface is improved, the degree of lithium precipitation is reduced, the rate performance and stability of the battery are enhanced, and the battery life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585937A_ABST
    Figure CN119585937A_ABST
Patent Text Reader

Abstract

The invention provides an isolating membrane and a preparation method thereof, a battery and an electric device. The isolating membrane comprises a first isolating membrane base material and a modification layer located on the surface of the first isolating membrane base material, the modification layer contains doped graphene oxide, and the electronegativity of doped atoms in the doped graphene oxide is larger than or equal to 2.
Need to check novelty before this filing date? Find Prior Art

Description

Isolation film and preparation method thereof, battery and electrical device Technical Field

[0001] The present application relates to the field of batteries, and in particular to an isolation membrane and a preparation method thereof, a battery and an electrical device. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] During the use of the battery, as lithium ions are embedded in the negative electrode, the problem of lithium plating at the negative electrode is inevitable. The occurrence of the lithium plating problem will generate lithium dendrites on the surface of the negative electrode. The growth of lithium dendrites may destroy the solid electrolyte interface film, thereby reducing the cycle performance of the battery. Therefore, the lithium plating problem is a relatively important factor restricting battery performance. In order to reduce the degree of lithium plating at the negative electrode, the traditional method is often to start with the negative electrode, mainly by improving the materials of the negative electrode to reduce the degree of lithium plating. However, with the continuous deepening of the research on the negative electrode, the bottleneck of this improvement method has gradually emerged. At this time, how to further improve the lithium plating problem is of great significance to further improve the battery performance.

[0004] Summary of the Invention

[0005] Based on the above problems, the present application provides an isolation membrane and a preparation method, a battery and an electrical device.

[0006] In order to achieve the above objectives, the present application provides an isolation membrane, comprising a first isolation membrane substrate and a modified layer located on the surface of the first isolation membrane substrate, wherein the modified layer comprises doped graphene oxide, and the electronegativity of the doping atoms in the doped graphene oxide is ≥2.

[0007] In this application, a separator is designed to provide a modified layer comprising doped graphene oxide on the surface of the separator substrate, and the electronegativity of the doped atoms in the doped graphene oxide is ≥ 2. When the separator is applied to a secondary battery, the doped atoms have a strong electronegativity, which can have a certain inductive effect on the transport of lithium ions, causing the lithium ions to be close to the separator to a certain extent. This can play a certain regulatory role in the deposition of lithium ions on the negative electrode surface, improve the uniformity of lithium ion deposition on the negative electrode surface, and reduce the degree of lithium plating, providing a new idea for reducing the degree of lithium plating on the negative electrode.

[0008] In some embodiments, the dopant atoms account for a mass percentage of 1% to 15% of the doped graphene oxide. The mass percentage of dopant atoms in the doped graphene oxide within this range can reduce the following risks: too few dopant atoms may hinder the doping effect of the dopant atoms, and too many dopant atoms may destroy the intrinsic structure of the graphene oxide, reduce the number of oxidized functional groups on its surface, reduce the lyophilicity of the graphene oxide, and restrict the improvement of electrolyte wettability.

[0009] In some embodiments, the dopant atoms include at least one of F atoms, N atoms, S atoms, and B atoms. These dopant atoms have a good inducing effect on the transport of lithium ions, facilitating the regulation of lithium ion transport. Furthermore, these dopant atoms are readily available, facilitating the production of corresponding doped graphene oxide.

[0010] In some embodiments, the doped graphene oxide includes at least one of granular doped graphene oxide and flake doped graphene oxide. Granular doped graphene oxide and flake doped graphene oxide can provide larger gaps for the transmission of lithium ions, which is beneficial for improving the ionic conductivity of the separator.

[0011] In some embodiments, the Dv50 of the granular doped graphene oxide is 0.5 μm to 5 μm. When the Dv50 of the granular doped graphene oxide is within the above range, the granular doped graphene oxide is not easy to penetrate into the other side of the first isolation membrane substrate, which is conducive to maintaining the stability of the isolation membrane structure.

[0012] In some embodiments, the flake-doped graphene oxide has a thickness of 0.5 nm to 3 nm and a flake diameter of 0.2 μm to 10 μm. When the thickness and diameter of the flake-doped graphene oxide are within these ranges, the flake-doped graphene oxide is less likely to penetrate into the other side of the first isolation membrane substrate, thereby maintaining the stability of the isolation membrane structure.

[0013] In some embodiments, the porosity of the modified layer is 5% to 30%. When the porosity of the modified layer is within this range, it can provide a larger porosity for the separator, which is beneficial to accelerate the transmission of lithium ions and further improve the performance of the battery.

[0014] In some embodiments, the thickness of the modification layer is 2 μm to 5 μm. If the thickness of the modification layer is too small, the improvement effect on the performance of the separator is poor. If the thickness of the modification layer is too large, the thickness of the separator may be excessively increased, thereby increasing the volume of the battery.

[0015] In some embodiments, the material of the first separator substrate includes a polymer material. The polymer material can improve the isolation effect of the separator and help improve the stability of the battery.

[0016] In some embodiments, the polymer material includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride. These polymer materials have relatively stable properties and are widely available.

[0017] In some embodiments, the weight average molecular weight of the polymer material is 100,000 to 1,000,000. If the weight average molecular weight is too small, the performance of the polymer material may be poor, and if the weight average molecular weight is too large, the polymer material may be difficult to process and difficult to obtain.

[0018] In some embodiments, the porosity of the first separator substrate is 40% to 80%. The porosity of the first separator substrate within this range is conducive to accelerating the transmission of lithium ions and further improving the performance of the battery.

[0019] In some embodiments, the thickness of the first separator substrate is 3 μm to 30 μm. If the thickness of the first separator substrate is too small, the basic performance of the separator may be poor. If the thickness of the first separator substrate is too large, the thickness of the separator may be excessively increased, thereby increasing the volume of the battery.

[0020] In some embodiments, the thickness of the first separator substrate is 5 μm to 25 μm. The thickness of the first separator substrate within this range can achieve both good separator basic performance and suitable battery volume.

[0021] In some embodiments, the separator further includes a second separator substrate, which is located on the surface of the modified layer away from the first separator substrate. In this case, the separator effectively prevents the modified layer from directly contacting the positive and negative electrodes, thereby reducing the risk of side reactions between the active material on the electrode and the graphene oxide.

[0022] In some embodiments, the material of the second separator substrate includes a polymer material, which can improve the isolation effect of the separator and enhance the internal stability of the battery.

[0023] In some embodiments, the polymer material includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride. These polymer materials have relatively stable properties and are widely available.

[0024] In some embodiments, the weight average molecular weight of the polymer material is 100,000 to 1,000,000. If the weight average molecular weight is too small, the performance of the polymer material may be poor, and if the weight average molecular weight is too large, the polymer material may be difficult to process and difficult to obtain.

[0025] In some embodiments, the porosity of the second separator substrate is 40% to 80%. The porosity of the second separator substrate within this range is conducive to accelerating the transmission of lithium ions and further improving the performance of the battery.

[0026] In some embodiments, the thickness of the second separator substrate is 3 μm to 30 μm. If the thickness of the second separator substrate is too small, the basic performance of the separator may be poor. If the thickness of the second separator substrate is too large, the thickness of the separator may be excessively increased, thereby increasing the volume of the battery.

[0027] In some embodiments, the thickness of the second separator substrate is 5 μm to 25 μm. The thickness of the second separator substrate within this range can achieve both good separator basic performance and suitable battery volume.

[0028] In some embodiments, the modified layer further comprises a binder. When the modified layer further comprises a binder, the binding between the modified layer and the isolation membrane substrate and between the graphene oxide can be promoted.

[0029] In some embodiments, the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyvinylidene fluoride. These binders have good bonding properties and good compatibility with the separator substrate and the modified layer.

[0030] In some embodiments, the mass ratio of the binder to the doped graphene oxide is (0.01-0.05): 1. If the amount of the binder is too small, poor bonding performance may occur, while if the amount of the binder is too large, the doping amount of the doping atoms may be too small, thereby limiting the effect of the doping atoms.

[0031] In some embodiments, the modified layer further contains a dispersant. When the modified layer further contains a dispersant, the uniformity of distribution of various materials in the modified layer can be improved, thereby enhancing the stability of the isolation membrane performance.

[0032] In some embodiments, the dispersant includes at least one of polyethyleneimine and its derivatives, hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, and polyethylene glycol. These dispersants have good dispersibility and good compatibility with the isolation membrane substrate and the modified layer.

[0033] Optionally, the mass ratio of the dispersant to the doped graphene oxide is (0.01-0.08): 1. If the amount of the dispersant is too small, the dispersant performance may be poor, and if the amount of the dispersant is too large, the doping amount of the doping atoms may be too small, thereby limiting the effect of the doping atoms.

[0034] In some embodiments, the modified layer further comprises a thickener. When the modified layer further comprises a thickener, the stability of the materials in the modified layer can be improved, thereby enhancing the stability of the isolation membrane performance.

[0035] In some embodiments, the thickener includes at least one of sodium hydroxymethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, polyacrylate, polyurethane, and polyether. These thickeners have good thickening properties and are well compatible with the isolation membrane substrate and the modified layer.

[0036] In some embodiments, the mass ratio of the thickener to the doped graphene oxide is (0.005-0.05): 1. If the amount of the thickener is too small, the thickener performance may be poor, and if the amount of the thickener is too large, the doping amount of the doping atoms may be too small, thereby limiting the effect of the doping atoms.

[0037] The present application also provides a method for preparing an isolation membrane, comprising the steps of applying a slurry comprising doped graphene oxide to the surface of a first isolation membrane substrate and curing the slurry to form a modified layer comprising the graphene oxide on the corresponding surface of the first isolation membrane substrate, wherein the electronegativity of the dopant atoms in the doped graphene oxide is ≥ 2. This preparation method can produce an isolation membrane with good performance and is simple and easy to implement.

[0038] In some embodiments, after applying the slurry containing doped graphene oxide to the surface of the first isolation membrane substrate and before curing, the following step is further included: covering the surface of the slurry with a second isolation membrane substrate. In this manner, an isolation membrane having a sandwich structure of "first isolation membrane substrate-modified layer-second isolation membrane substrate" can be prepared, resulting in an isolation membrane with improved performance.

[0039] In some embodiments, the curing comprises hot pressing and drying in sequence. The hot pressing and drying curing method is conducive to obtaining a separator with good performance, is simple to operate, and is conducive to improving the preparation efficiency of the separator.

[0040] In some embodiments, the hot pressing temperature is 120° C. to 150° C. If the hot pressing temperature is too low, it may be difficult to obtain a good hot pressing effect, while if the hot pressing temperature is too high, the structure of the isolation membrane may be damaged, which may have an adverse effect on the performance of the isolation membrane.

[0041] In some embodiments, the hot pressing pressure is 3 MPa to 8 MPa. If the hot pressing pressure is too low, it may be difficult to obtain a good hot pressing effect. If the hot pressing pressure is too high, the structure of the isolation membrane may be damaged, which may have an adverse effect on the performance of the isolation membrane.

[0042] In some embodiments, the hot pressing time is 1 to 5 minutes. If the hot pressing time is too short, it may be difficult to obtain a good hot pressing effect, and if the hot pressing time is too long, it may extend the preparation time and reduce the preparation efficiency of the isolation membrane.

[0043] In some embodiments, the drying temperature is 90° C. to 120° C. If the drying temperature is too low, it may be difficult to obtain a good hot pressing effect, while if the drying temperature is too high, the structure of the separator may be damaged, which may have an adverse effect on the performance of the separator.

[0044] In some embodiments, the drying time is 6 hours to 12 hours. If the drying time is too short, it may be difficult to obtain a good drying effect, and if the drying time is too long, the preparation time may be prolonged, thereby reducing the preparation efficiency of the isolation membrane.

[0045] In some embodiments, the drying is performed under vacuum conditions, which is beneficial for improving the drying effect and obtaining a separator with good performance.

[0046] The present application also provides a battery comprising the above-mentioned separator or the separator prepared by the above-mentioned separator preparation method. The introduction of the above-mentioned separator or the separator prepared by the above-mentioned separator preparation method can enable the battery to have good rate performance.

[0047] The present application also provides an electrical device comprising the above-mentioned battery. By introducing the above-mentioned battery, the electrical device can have good electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0049] FIG1 is a schematic diagram of a battery according to one embodiment of the present application.

[0050] FIG2 is an exploded view of the battery shown in FIG1 according to one embodiment of the present application.

[0051] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0052] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.

[0053] FIG5 is an exploded view of the battery pack shown in FIG4 according to an embodiment of the present application.

[0054] FIG6 is a schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application.

[0055] FIG7 is a schematic diagram of an isolation membrane according to an embodiment of the present application.

[0056] FIG8 is a schematic diagram of an isolation membrane according to another embodiment of the present application.

[0057] Description of reference numerals:

[0058] 1. Battery pack; 2. Upper case; 3. Lower case; 4. Battery module; 5. Battery; 51. Housing; 52. Electrode assembly; 53. Cover plate; 6. Electrical device; 7. Isolation membrane; 71. First isolation membrane substrate; 72. Modification layer; 73. Second isolation membrane substrate.

[0059] In order to better describe and illustrate the embodiments and / or examples of the inventions disclosed herein, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered to limit the scope of the disclosed inventions, the presently described embodiments and / or examples, and any of the best modes currently understood for these inventions. DETAILED DESCRIPTION

[0060] To facilitate understanding of the present application, a more comprehensive description of the present application will be provided below with reference to the accompanying drawings. The accompanying drawings illustrate preferred embodiments of the present application. However, the present application may be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and comprehensive understanding of the disclosure of the present application.

[0061] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application pertains. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0062] The "ranges" disclosed herein are defined in terms of lower and upper limits, where a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values ​​and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 to 120 and 80 to 110 are listed for a particular parameter, it is understood that ranges of 60 to 110 and 80 to 120 are also contemplated. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, the following ranges are all contemplated: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise indicated, the numerical range "a to b" is a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0063] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0064] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0065] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0066] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0067] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true or present, and B is false or absent; A is false or absent, and B is true or present; or both A and B are true, or both A and B are present.

[0068] Unless otherwise indicated, the terms used in this application have the commonly understood meanings generally understood by those skilled in the art. Unless otherwise indicated, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art. For example, the tests can be performed using the methods described in the examples of this application.

[0069] Referring to FIG. 7 , one embodiment of the present application provides an isolation membrane 7 . The isolation membrane 7 includes a first isolation membrane substrate 71 and a modified layer 72 disposed on a surface of the first isolation membrane substrate 71 . The modified layer 72 includes doped graphene oxide, where the electronegativity of the dopant atoms in the doped graphene oxide is ≥ 2. In FIG. 7 , the doped graphene oxide is not shown.

[0070] In the above embodiment, the separator is designed to provide a modified layer comprising doped graphene oxide on the surface of the separator substrate, and the electronegativity of the dopant atoms in the doped graphene oxide is ≥ 2. When the separator is applied to a secondary battery, the dopant atoms have a strong electronegativity, which can have a certain inductive effect on the transport of lithium ions, causing the lithium ions to approach the separator to a certain extent. This can play a certain regulatory role in the deposition of lithium ions on the negative electrode surface, improve the uniformity of lithium ion deposition on the negative electrode surface, and reduce the degree of lithium plating, providing a new approach to reducing the degree of lithium plating on the negative electrode.

[0071] It is understood that the electronegativity in this application refers to the electronegativity of the Pauling scale. Optionally, the electronegativity of the doping atoms in the doped graphene oxide is ≥2.5.

[0072] Furthermore, when lithium ions form lithium on the separator, graphene oxide can react with the lithium to avoid the continued generation of lithium, thus avoiding the growth of lithium dendrites on the separator, thereby avoiding the problem of lithium dendrites piercing the entire separator and causing a short circuit. Specifically, when lithium ions form lithium on the side of the modified layer away from the first separator substrate, the lithium can react with graphene oxide and be consumed, reducing the risk of lithium dendrite growth, thereby reducing the risk of growing lithium dendrites piercing the entire separator. When lithium ions form lithium on the side of the first separator substrate away from the modified layer, as the lithium dendrites grow, they may pierce the first separator substrate. Then, the lithium dendrites come into contact with the modified layer. At this time, graphene oxide can react with the lithium dendrites and consume the lithium dendrites, thereby reducing the risk of continued growth of lithium dendrites. In this way, even if the lithium dendrites pierce the first separator substrate, they will not pierce the modified layer, which effectively reduces the risk of lithium dendrites piercing the entire separator.

[0073] As an example of the reaction between lithium and graphene oxide, the reaction between lithium and graphene oxide can be expressed as the reaction formula shown in formula (1): GO+Li→rGO+Li2O Formula (1)

[0074] In formula (1), GO represents graphene oxide, and rGO represents reduced graphene oxide. That is, when lithium comes into contact with graphene oxide, the lithium reacts with the graphene oxide and is consumed, effectively reducing the risk of continued growth of lithium dendrites.

[0075] Furthermore, the doped atoms in the modified layer have strong electronegativity and can form hydrogen bonds with hydrogen atoms on the surface of the first isolation membrane substrate. This can improve the bonding strength between the modified layer and the first isolation membrane substrate, and also improve the bonding strength between graphene oxide and graphene oxide, thereby improving the structural stability of the isolation membrane.

[0076] At the same time, graphene oxide has oxygen-containing functional groups such as hydroxyl, carboxyl, and aldehyde, which shows good lyophilicity, and the polarity of the doped atoms in the modified layer is strong, which can improve the lyophilic properties of the isolation membrane surface, increase the affinity between the isolation membrane and the electrolyte, and promote better infiltration of the electrolyte into the isolation membrane, which is beneficial to reduce the internal resistance of the battery and shorten the formation time of the battery.

[0077] In some embodiments, the mass percentage of doping atoms in the doped graphene oxide is 1% to 15%. When the mass percentage of doping atoms in the doped graphene oxide is within the above range, the following risks can be reduced: too few doping atoms make it difficult to achieve the doping effect of the doping atoms, and too much doping atoms in the doped graphene oxide may destroy the intrinsic structure of the graphene oxide, reduce the number of oxidized functional groups on its surface, reduce the lyophilicity of the graphene oxide, and restrict the improvement of the electrolyte wettability. In addition, when the mass percentage of doping atoms in the doped graphene oxide is within the above range, the amount of graphene oxide will not be reduced, the ability of the modified layer to consume lithium elemental substances and the effect of the modified layer consuming lithium elemental substances are enhanced, and the effect of suppressing the continued growth of lithium dendrites is improved. Optionally, the mass percentage of doping atoms in the doped graphene oxide is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.

[0078] Optionally, the doping atoms include at least one of F atoms, N atoms, S atoms and B atoms. It is understandable that atoms have their own electronegativity, which can be obtained through the Pauling electronegativity table. Among them, the electronegativity of F atoms is 3.98. The electronegativity of N atoms is 3.04. The electronegativity of S atoms is 2.58. The electronegativity of B atoms is 2.04. These doping atoms have a good inductive effect on the transport of lithium ions, which facilitates the regulation of the transport of lithium ions. In addition, the sources of these doping atoms are easy to obtain, which facilitates the acquisition of corresponding doped graphene oxide.

[0079] In some embodiments, the doped graphene oxide includes at least one of granular doped graphene oxide and flake doped graphene oxide. Granular doped graphene oxide and flake doped graphene oxide can provide larger gaps for the transmission of lithium ions, which is beneficial to improving the ionic conductivity of the isolation membrane. It is understandable that the doped graphene oxide can be compounded by micro-oxidation treatment. Optionally, the micro-oxidation treatment includes: cooling concentrated sulfuric acid to -10°C, stirring and mixing sodium nitrate with doped graphene oxide, stirring and then standing, adjusting the pH to 4-5 and then drying, and then heat treating, which can improve the surface oxidation. Optionally, the micro-oxidation treatment includes: cooling 200mL concentrated sulfuric acid (98wt%, analytical grade) to -10°C using a low-temperature coolant circulation pump, stirring and mixing 10g sodium nitrate (analytical grade) with 20g doped graphene oxide, stirring and then standing for 12h, adjusting the pH to 4-5 and then drying at 90°C, and heat treating at 200°C for 10min, which can improve the surface oxidation.

[0080] Optionally, the Dv50 of the granular doped graphene oxide is 0.5 μm to 5 μm. For example, the Dv50 of the granular doped graphene oxide is 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm, etc. When the Dv50 of the granular doped graphene oxide is within the range of 0.5 μm to 5 μm, the granular doped graphene oxide is less likely to penetrate into the other side of the first isolation membrane substrate, which is beneficial for maintaining the stability of the isolation membrane structure.

[0081] It is understood that in this application, Dv50 refers to the particle size corresponding to the 50% cumulative particle size distribution in the volume cumulative distribution curve. Its physical meaning is that particles with a smaller (or larger) size account for 50%. As an example, Dv50 can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd. in the UK, with reference to GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method.

[0082] Optionally, the thickness of the flake-doped graphene oxide is 0.5 nm to 3 nm, and the flake diameter is 0.2 μm to 10 μm. For example, the thickness of the flake-doped graphene oxide is 0.5 nm, 0.8 nm, 1 nm, 1.2 nm, 1.5 nm, 1.8 nm, 2 nm, 2.2 nm, 2.5 nm, 2.8 nm, 3 nm, etc. The flake diameter of the flake-doped graphene oxide is 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. When the thickness and flake diameter of the flake-doped graphene oxide are within the above ranges, the flake-doped graphene oxide is less likely to penetrate into the other side of the first isolation membrane substrate, which is beneficial to maintaining the stability of the isolation membrane structure.

[0083] It is understood that the doped graphene oxide comprises graphene oxide and dopant atoms. The dopant atoms are doped into the graphene oxide. The doped graphene oxide can be directly purchased from a commercial product or obtained by the following preparation method.

[0084] When the doping atom is fluorine, the preparation method of fluorine-doped graphene oxide (FGO) includes ultrasonically dispersing graphene oxide (GO) in deionized water to form a uniform dispersion. HNO3 and HF are then added to the dispersion, followed by heating, and the resulting solution is dried to obtain FGO. Optionally, the FGO is in the form of flakes with a thickness of 2 nm and a flake diameter of 0.2 μm to 10 μm.

[0085] Optionally, the heating temperature is 150° C. to 170° C., and the heating time is 8 to 15 hours. Further, the heating temperature is 150° C., 155° C., 160° C., 165° C., 170° C., etc., and the heating time is 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, etc.

[0086] Alternatively, a method for preparing F-doped graphene oxide (FGO) includes ultrasonically dispersing 50 mg of graphene oxide (GO) in 40 mL of deionized water to form a uniform dispersion. 0.5 mL of HNO3 and 9.5 mL of HF are then added to the dispersion, which is then transferred to a reactor and heated at 160°C for 12 hours. The resulting solution is then dried to obtain FGO.

[0087] When the doping atom is nitrogen, the preparation method of N-doped graphene oxide (NGO) includes grinding and mixing GO and melamine as precursors. The resulting mixture is heated in a protective gas atmosphere, then cooled, rinsed with water, and dried to obtain NGO. The NGO is preferably in the form of a sheet with a thickness of 0.8 nm to 1.2 nm and a diameter of 1 μm to 5 μm.

[0088] Optionally, the heating temperature is 700° C. to 900° C. Further, optionally, the heating temperature is 700° C., 750° C., 800° C., 850° C., 900° C., etc. Further, optionally, during heating, the mixture is heated from the initial temperature to 700° C. to 900° C. at a heating rate of 5° C. / min.

[0089] Alternatively, a method for preparing N-doped graphene oxide (NGO) includes thoroughly grinding and mixing 200 mg of GO and 1 g of melamine as precursors. The resulting mixture is heated to 800°C at a rate of 5°C / min in an argon atmosphere, followed by cooling, rinsing with water, and drying to obtain NGO.

[0090] When the doping atom is a sulfur atom, the preparation method of S-doped graphene oxide (SGO) includes: mixing GO and N,N-dimethylformamide to obtain a mixed solution, adding thionyl chloride to the mixed solution, stirring to react, then solid-liquid separation, washing, and drying to obtain SGO. Optionally, the SGO is in the form of flakes with a thickness of 1 nm to 2 nm and a flake diameter of 0.2 μm to 10 μm.

[0091] Optionally, the stirring reaction temperature is 50°C to 80°C, and the stirring reaction time is 12h to 36h. Further optionally, the stirring reaction temperature is 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0092] Further optionally, the preparation method of S-doped graphene oxide (SGO) includes: adding 0.1g to 1g of GO to 50mL to 100mL of N,N-dimethylformamide, ultrasonically dispersing for 20min to 40min to form a uniformly dispersed mixed solution, adding 10mL to 30mL of thionyl chloride to the mixed solution, reacting at 50°C to 80°C under mechanical stirring for 12h to 36h, and then centrifuging, washing, and drying to obtain SGO.

[0093] When the doping atom is a B atom, the preparation method of B-doped graphene oxide (BGO) includes: mixing GO with H3BO3, heating the obtained mixture, cooling it, washing it with water, and drying it to obtain BGO.

[0094] Optionally, when preparing BGO, the heating temperature is 250° C. to 300° C., the reaction pressure is 20 MPa to 22 MPa, the pH is 4.0 to 4.5, and the reaction time is 2 h to 5 h.

[0095] Further optionally, the preparation method of B-doped graphene oxide (BGO) includes: adding 0.25 g GO and 5 mL 2M H3BO3 into a reactor, controlling the reaction temperature at 250°C to 300°C, the reaction pressure at 20 MPa to 22 MPa, and the pH at 4.0-4.5, reacting for 2 hours, taking out, washing, and drying to obtain BGO.

[0096] In some embodiments, the porosity of the modified layer is 5% to 30%. This provides a greater porosity for the separator, which facilitates faster lithium ion transmission and further improves battery performance. Alternatively, the porosity of the modified layer can be 5%, 8%, 10%, 15%, 20%, 25%, 30%, etc.

[0097] In some embodiments, the thickness of the modified layer is 2 μm to 5 μm. Optionally, the thickness of the modified layer is 2 μm, 3 μm, 4 μm, 5 μm, etc. If the thickness of the modified layer is too small, the improvement effect on the performance of the separator will be poor. If the thickness of the modified layer is too large, the thickness of the separator may be excessively increased, thereby increasing the volume of the battery.

[0098] In some embodiments, the material of the first separator substrate includes a polymer material. The polymer material can improve the isolation effect of the separator and enhance the internal stability of the battery. Optionally, the polymer material includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride. These polymer materials have relatively stable performance and are widely available. Further optionally, the weight-average molecular weight of the polymer material is between 100,000 and 1,000,000. If the weight-average molecular weight is too low, the performance of the polymer material may be poor, while if the weight-average molecular weight is too high, the polymer material may be too difficult to process and difficult to obtain.

[0099] In some embodiments, the porosity of the first separator substrate is 40% to 80%. A porosity within this range facilitates the transport of lithium ions and further improves battery performance. For example, the porosity of the first separator substrate can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, and the like.

[0100] It is understood that the porosity test method in this application is: testing is carried out with reference to the standard GB / T 36363-2018.

[0101] In some embodiments, the thickness of the first separator substrate is 3 μm to 30 μm. If the thickness of the first separator substrate is too small, the basic performance of the separator may be poor. If the thickness of the first separator substrate is too large, the thickness of the separator may be excessively increased, increasing the volume of the battery. For example, the thickness of the first separator substrate is 3 μm, 5 μm, 8 μm, 10 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, 28 μm, 30 μm, etc. Optionally, the thickness of the first separator substrate is 5 μm to 25 μm. Within this range, the thickness of the first separator substrate can achieve both good basic performance of the separator and a suitable battery volume.

[0102] Referring to Figure 8 , in some embodiments, the separator 7 further includes a second separator substrate 73 , which is located on the surface of the modified layer 72 away from the first separator substrate 71 . In this case, the separator 7 can have a sandwich structure consisting of "first separator substrate 71 - modified layer 72 - second separator substrate 73 ." The separator effectively prevents the modified layer from directly contacting the positive and negative electrodes, thereby reducing the risk of side reactions between the active material on the electrode and the graphene oxide. These side reactions consume lithium, reducing battery capacity and cycle life. This sandwich structure reduces lithium consumption due to side reactions, helping to maintain battery capacity and cycle life. Furthermore, the sandwich structure provides a more stable structure, which can enhance the stability of the separator and battery structure and performance.

[0103] In some embodiments, the material of the second separator substrate includes a polymer material. The polymer material can improve the isolation effect of the separator and enhance the internal stability of the battery. Optionally, the polymer material includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl chloride. These polymer materials have relatively stable performance and are widely available. Further optionally, the weight-average molecular weight of the polymer material is between 100,000 and 1,000,000. If the weight-average molecular weight is too low, the performance of the polymer material may be poor, while if the weight-average molecular weight is too high, the polymer material may be too difficult to process and difficult to obtain.

[0104] Optionally, the second separator substrate has a porosity of 40% to 80%. A porosity within this range facilitates the transport of lithium ions and further improves battery performance. For example, the porosity of the second separator substrate can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, and the like.

[0105] Optionally, the thickness of the second separator substrate is 3μm to 30μm. If the thickness of the second separator substrate is too small, the basic performance of the separator may be poor. If the thickness of the second separator substrate is too large, the thickness of the separator may be excessively increased, increasing the volume of the battery. For example, the thickness of the second separator substrate is 3μm, 5μm, 8μm, 10μm, 15μm, 18μm, 20μm, 23μm, 25μm, 28μm, 30μm, etc. Optionally, the thickness of the second separator substrate is 5μm to 25μm. Within this range, the thickness of the second separator substrate can achieve both good basic performance of the separator and a suitable battery volume.

[0106] It is understood that the first separator substrate and the second separator substrate may be the same or different.

[0107] In some embodiments, the modified layer also contains a binder. Optionally, the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyvinylidene fluoride. These binders have good bonding properties and are well compatible with the isolation membrane substrate and the modified layer. Further optionally, the mass ratio of the binder to the doped graphene oxide is (0.01-0.05):1. If the amount of binder is too small, the bonding performance may be poor. If the amount of binder is too large, the doping amount of doping atoms may be too small, which limits the effect of the doping atoms. When the modified layer also contains a binder, the presence of doping atoms in the modified layer can promote the bonding between the modified layer and the isolation membrane substrate and between the graphene oxide. Therefore, while maintaining the bonding strength, the presence of doping atoms can reduce the use of binder. Optionally, the mass ratio of the binder to the doped graphene oxide is 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, etc.

[0108] In some embodiments, the modified layer further contains a dispersant. When the modified layer further contains a dispersant, the uniformity of dispersion of the materials in the modified layer can be improved, thereby enhancing the stability of the isolation membrane performance.

[0109] Optionally, the dispersant includes at least one of polyethyleneimine and its derivatives, hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, and polyethylene glycol. These dispersants have good dispersibility and good compatibility with the isolation membrane substrate and the modified layer.

[0110] Furthermore, optionally, the mass ratio of the dispersant to the doped graphene oxide is (0.01-0.08):1. Using too little dispersant may result in poor dispersant performance, while using too much dispersant may result in too little doping of the doping atoms, limiting the effect of the doping atoms. Alternatively, the mass ratio of the dispersant to the doped graphene oxide is 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, and the like.

[0111] In some embodiments, the modified layer further comprises a thickener, which can improve the stability of the materials in the modified layer and enhance the stability of the isolation membrane performance.

[0112] Optionally, the thickener includes at least one of sodium hydroxymethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, polyacrylate, polyurethane and polyether. These thickeners have good thickening properties and good compatibility with the isolation membrane substrate and the modified layer.

[0113] Further optionally, the mass ratio of the thickener to the doped graphene oxide is (0.005-0.05):1. If the amount of thickener is too small, the thickener performance may be poor. If the amount of thickener is too large, the doping amount of the doping atoms may be too small, thereby limiting the effect of the doping atoms. Optionally, the mass ratio of the thickener to the doped graphene oxide is 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1, 0.05:1, etc.

[0114] Another embodiment of the present application provides a method for preparing an isolation membrane, comprising the steps of applying a slurry comprising doped graphene oxide to the surface of a first isolation membrane substrate and curing the slurry to form a modified layer comprising graphene oxide on the corresponding surface of the first isolation membrane substrate, wherein the electronegativity of the dopant atoms in the doped graphene oxide is ≥ 2.0. This preparation method can produce an isolation membrane with good performance and is simple and easy to implement.

[0115] Optionally, after applying the slurry containing doped graphene oxide to the surface of the first isolation membrane substrate and before curing, the following step is further included: covering the surface of the slurry with a second isolation membrane substrate. In this case, an isolation membrane having a sandwich structure of "first isolation membrane substrate-modified layer-second isolation membrane substrate" can be produced, resulting in an isolation membrane with improved performance.

[0116] In some embodiments, curing includes sequentially performing hot pressing and drying. The hot pressing and drying curing method is conducive to obtaining a separator with good performance, is simple to operate, and is conducive to improving the preparation efficiency of the separator.

[0117] Optionally, the hot pressing temperature is 120°C to 150°C. A hot pressing temperature that is too low may not achieve a good hot pressing effect, while a hot pressing temperature that is too high may damage the structure of the separator and adversely affect the performance of the separator. For example, the hot pressing temperature is 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, etc.

[0118] Optionally, the hot pressing pressure is 3 MPa to 8 MPa. If the hot pressing pressure is too low, it may be difficult to achieve a good hot pressing effect. If the hot pressing pressure is too high, the structure of the separator may be damaged, adversely affecting the performance of the separator. For example, the hot pressing pressure is 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, etc.

[0119] Optionally, the hot pressing time is 1 to 5 minutes. If the hot pressing time is too short, it may be difficult to achieve a good hot pressing effect. If the hot pressing time is too long, it may extend the preparation time and reduce the efficiency of the separator preparation. For example, the hot pressing time is 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, etc.

[0120] In some embodiments, the drying temperature is 90°C to 120°C. A drying temperature that is too low may make it difficult to achieve a good hot pressing effect, while a drying temperature that is too high may damage the structure of the separator, adversely affecting the performance of the separator. For example, the drying temperature is 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, etc.

[0121] Optionally, the drying time is 6 to 12 hours. A drying time that is too short may not achieve a good drying effect, while a drying time that is too long may extend the preparation time and reduce the efficiency of the separator preparation. For example, the drying time is 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.

[0122] Further optionally, the drying is performed under vacuum conditions, which is beneficial for improving the drying effect and obtaining a separator with good performance.

[0123] It is understood that the slurry containing doped graphene oxide also includes at least one of a binder, a dispersant, and a thickener. The materials and amounts of the binder, dispersant, and thickener can be selected accordingly in the above-mentioned isolation membrane and will not be further described here.

[0124] It is also understood that the slurry comprising doped graphene oxide further comprises a solvent. Optionally, the solvent comprises one or more of water, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and dimethylacetamide (DMAC). Optionally, in the slurry comprising doped graphene oxide, the mass ratio of doped graphene oxide to solvent is (0.5-5):100. For example, the mass ratio of doped graphene oxide to solvent is 0.5:100, 1:100, 2:100, 3:100, 4:100, 5:100, etc.

[0125] In some embodiments, a method for preparing a slurry comprising doped graphene oxide includes stirring and mixing the doped graphene oxide and a solvent. Optionally, the stirring and mixing speed is 700 rpm to 1000 rpm. It is understood that at least one of a binder, a dispersant, and a thickener may be added during the stirring and mixing as needed.

[0126] Another embodiment of the present application provides a battery comprising the above-mentioned separator or the separator prepared by the above-mentioned separator preparation method. The introduction of the above-mentioned separator or the separator prepared by the above-mentioned separator preparation method can enable the battery to have good rate performance.

[0127] The present application also provides a battery module, which includes the above-mentioned battery.

[0128] The present application also provides a battery pack, which includes the above-mentioned battery or the above-mentioned battery module.

[0129] The present application also provides an electrical device comprising at least one of the aforementioned battery, battery module, and battery pack. The introduction of at least one of the aforementioned battery, battery module, and battery pack can provide the electrical device with good electrical performance.

[0130] The battery, battery module, battery pack and power-consuming device of the present application are described below with appropriate reference to the accompanying drawings. It is understood that the battery of the present application can be a secondary battery.

[0131] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.

[0132] Positive electrode

[0133] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0134] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is provided on either or both of the two facing surfaces of the positive electrode current collector.

[0135] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate. Alternatively, the metal material may include but is not limited to one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Alternatively, the polymer material substrate may include but is not limited to one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0136] As an example, the positive electrode active material may include positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include but are not limited to at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Optionally, lithium cobalt oxide includes LiCoO2. Lithium nickel oxide includes LiNiO2. Lithium manganese oxide includes at least one of LiMnO2 and LiMn2O4. Lithium nickel cobalt manganese oxide includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2O2(NCM 622 ) and LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ) at least one of. Lithium nickel cobalt aluminum oxide includes LiNi 0.85 Co 0.15 Al 0.05 O2. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon. Optionally, the lithium iron phosphate includes LiFePO4 (LFP). The lithium manganese phosphate includes LiMnPO4. The weight ratio of the positive electrode active material in the positive electrode film layer is 80 to 100 weight percent, based on the total weight of the positive electrode film layer.

[0137] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0 to 20 weight%, based on the total weight of the positive electrode film layer.

[0138] In some embodiments, the positive electrode film layer may also optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0 to 20% by weight, based on the total weight of the positive electrode film layer.

[0139] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry. Optionally, the solvent includes N-methylpyrrolidone. The positive electrode slurry has a solid content of 40 to 80 wt %, and the viscosity at room temperature is adjusted to 5000 to 25000 mPa·s. The positive electrode slurry is coated on the surface of the positive electrode current collector, dried, and then cold-pressed by a cold rolling mill to form a positive electrode sheet; the positive electrode powder coating unit surface density is 150-350 mg / m 2 The compaction density of the positive electrode is 3.0-3.6g / cm 3 , optional 3.3-3.5g / cm 3 The calculation formula of the compaction density is: compaction density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).

[0140] It is understandable that the positive electrode sheet in the embodiment of the present application can be made by using the above-mentioned positive electrode sheet as the positive electrode sheet body and forming a solid electrolyte interface film on the surface of the positive electrode sheet body.

[0141] Negative electrode

[0142] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0143] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0144] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material on a polymer base material. Optionally, the metal material includes at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0145] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70 to 100 weight %, based on the total weight of the negative electrode film layer.

[0146] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0 to 30% by weight, based on the total weight of the negative electrode film layer.

[0147] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0 to 20% by weight, based on the total weight of the negative electrode film layer.

[0148] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener. The weight ratio of the other additives in the negative electrode film layer is 0 to 15% by weight, based on the total weight of the negative electrode film layer. Optionally, the thickener includes sodium carboxymethylcellulose (CMC-Na).

[0149] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a negative electrode slurry. Optionally, the solvent includes deionized water. The solid content of the negative electrode slurry is 30 to 70 wt%, and the viscosity at room temperature is adjusted to 2000 to 10000 mPa·s; the obtained negative electrode slurry is coated on the negative electrode current collector, and after a drying process, cold pressing, such as rolling, is performed to obtain a negative electrode sheet. The negative electrode powder coating unit area density is 75 to 220 mg / m 2 , the compaction density of the negative electrode is 1.2~2.0g / m 3 .

[0150] It can be understood that the negative electrode sheet in the embodiment of the present application can be made by using the above-mentioned negative electrode sheet as the negative electrode sheet body and forming a solid electrolyte interface film on the surface of the negative electrode sheet body.

[0151] electrolytes

[0152] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0153] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0154] In some embodiments, the electrolyte salt may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte salt is typically 0.5 to 5 mol / L.

[0155] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0156] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0157] Isolation film

[0158] In some embodiments, the secondary battery further includes a separator. This application does not specifically limit the type of separator; any known porous separator with good chemical and mechanical stability may be used. The separator may be the separator described above or a separator prepared using the above-described separator preparation method.

[0159] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0160] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0161] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0162] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic. Examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate. This application does not particularly limit the shape of the secondary battery, which can be cylindrical, square, or any other shape. For example, Figure 1 shows a secondary battery 5 with a square structure as an example.

[0163] In some embodiments, referring to Figure 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0164] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0165] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0166] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0167] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0168] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0169] In addition, the present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0170] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0171] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0172] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0173] Example

[0174] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the application will be further described in detail below with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0175] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.

[0176] Example 1

[0177] In this embodiment, the doping atoms are F atoms, and the doping atoms account for 3% by mass of the doped graphene oxide. The doped graphene oxide is purchased from a commercial company. The doped graphene oxide is in the form of flakes with a thickness of 2 nm and a flake diameter of 0.2 μm to 10 μm.

[0178] The method for preparing the isolation film in this embodiment includes:

[0179] (1) 2 g of doped graphene oxide was evenly dispersed in 100 g of water and ultrasonically dispersed for 2 h to obtain a uniform dispersion.

[0180] (2) 0.1 g of sodium carboxymethyl cellulose (sodium carboxymethyl cellulose is used as a binder and a thickener, wherein the binder and the thickener are 0.05 g of sodium carboxymethyl cellulose, respectively) and 0.1 g of hydrolyzed polymaleic anhydride are added to the dispersion obtained in (1), and magnetic stirring is carried out at 800 rpm for 2 h to obtain a slurry including doped graphene oxide.

[0181] (3) The slurry obtained in (2) was evenly coated on a 7 μm thick polypropylene (PP) film. Another 7 μm thick PP film was taken to cover the surface of the slurry. The slurry was hot pressed and vacuum dried to obtain the isolation film of this embodiment. The hot pressing temperature was 120°C, the hot pressing pressure was 5 MPa, and the hot pressing time was 5 minutes. The vacuum drying temperature was 100°C and the vacuum drying time was 12 hours. The weight average molecular weight of the polypropylene was 100,000 to 1,000,000.

[0182] In this embodiment, the isolation film substrate is a two-layered structure, and the isolation film is a sandwich structure of isolation film substrate-modification layer-isolation film substrate. The thickness of the isolation film is 17 μm, of which the thickness of the modification layer is 3 μm.

[0183] Example 2

[0184] Compared to Example 1, this example differs in that the preparation method of doped graphene oxide includes ultrasonically dispersing graphene oxide in deionized water to form a uniform dispersion. HNO3 and HF are then added to the dispersion, which is then transferred to a reactor and heated at 160°C for 12 hours. The reacted solution is dried to obtain doped graphene oxide. The graphene oxide is XF096 graphene oxide from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0185] Example 3 to Example 13

[0186] Compared to Example 1, Examples 3 to 13 differ in the doping atoms and / or the mass percentage of the doping atoms in the doped graphene oxide. The doped graphene oxide was prepared by using the above-described methods for preparing FGO, NGO, SGO, and BGO. The graphene oxide was XF096 graphene oxide from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd. The details are shown in Table 1.

[0187] Example 14

[0188] Compared with Example 1, the difference of Example 14 is:

[0189] The method for preparing the isolation film in this embodiment includes:

[0190] (1) 2 g of doped graphene oxide was evenly dispersed in 100 g of water and ultrasonically dispersed for 2 h to obtain a uniform dispersion.

[0191] (2) 0.1 g of sodium carboxymethyl cellulose (sodium carboxymethyl cellulose is used as a binder and a thickener, wherein the binder and the thickener are 0.05 g of sodium carboxymethyl cellulose, respectively) and 0.1 g of hydrolyzed polymaleic anhydride are added to the dispersion obtained in (1), and magnetic stirring is carried out at 800 rpm for 2 h to obtain a slurry including doped graphene oxide.

[0192] (3) The slurry obtained in (2) was evenly coated on a 7 μm thick polypropylene (PP) film, and then hot-pressed and vacuum-dried to obtain the isolation film of this embodiment. The hot-pressing temperature was 120°C, the hot-pressing pressure was 5 MPa, and the hot-pressing time was 5 minutes. The vacuum drying temperature was 100°C, and the vacuum drying time was 12 hours. The weight-average molecular weight of the polypropylene was 100,000 to 1,000,000.

[0193] In this embodiment, the isolation film substrate is a single layer, and the isolation film has a structure of isolation film substrate-modification layer. The thickness of the isolation film is 10 μm, of which the thickness of the modification layer is 3 μm.

[0194] Example 15

[0195] Compared with Example 14, the difference of this example is that the thickness of the polypropylene film is 14 μm, the thickness of the isolation film is 17 μm, and the thickness of the modification layer is 3 μm.

[0196] Comparative Example 1

[0197] Compared with Example 1, the difference of this comparative example is that the doped graphene oxide is replaced by undoped graphene oxide.

[0198] Comparative Example 2

[0199] Compared with Example 1, the difference of this comparative example is that the doped graphene oxide is replaced by graphene.

[0200] Comparative Example 3

[0201] Compared with Example 1, the difference of this comparative example is that no doped graphene oxide is added to the slurry.

[0202] Comparative Example 4

[0203] Compared with Example 1, the difference of this comparative example is that the doping atom is replaced by gallium (Ga) with an electronegativity of 1.81 instead of F.

[0204] Test Case

[0205] (1) Release Film Peel Force Test: A 20 mm wide standard tape (31B) was applied to one surface of the release film using a roller press at a constant stress of 2 kg and 300 mm / min. A 180-degree peel test was performed using a tensile testing machine at a speed of 300 mm / min. Peel force values ​​were obtained at 50 points over a test distance of 50 to 120 mm, and the average value was calculated. The peel force indicates the degree of adhesion between the decorative layer and the release film substrate; a greater peel force indicates better adhesion between the decorative layer and the release film substrate. The results are shown in Table 1.

[0206] (2) Isolator Wetting Angle Test: The test isolator was cut into 50 mm x 50 mm pieces. 1 ml of standard electrolyte was dropped onto the sample, and the angle between the droplet and the isolator was observed using a contact angle meter. The standard electrolyte consisted of 1 mol / L LiPF6 dissolved in ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a weight ratio of 1:1:1. The results are shown in Table 1.

[0207] (3) Electrolyte absorption rate test of the separator: The separator was immersed in the electrolyte for 60 minutes. The separator was taken out and dried every 10 minutes and then the separator weight was measured. The electrolyte absorption rate can be calculated as (separator weight after absorption - initial separator weight) / initial separator weight. The higher the electrolyte absorption rate, the better the separator wettability. The results are shown in Table 1.

[0208] (4) Rate performance test of the battery corresponding to the isolation membrane:

[0209] ① Discharge rate testing was conducted using CR2025 button-type batteries. The positive electrode used lithium iron phosphate (LIFP) with a binder ratio of 8:1:1 for LFP:conductive carbon black:PVDF. The negative electrode used a lithium sheet. The electrolyte used was 1 mol / L LiPF6, and the weight ratio of EC:DEC in the solvent was 1:1. The separator used was the same as that used in the Examples and Comparative Examples.

[0210] ② Charging conditions: The battery was charged at room temperature using the constant current-constant voltage (CC-CV) mode. First, charge in the constant current mode at a fixed current of 0.5C until the voltage reaches 3.65V. Then, switch to the constant voltage mode with a cutoff current of 0.02C to fully charge the battery.

[0211] ③Discharge conditions: Discharge in constant current mode to 2.5V at different discharge rates (C-rate: 0.1C / 5C) and cycle 100 times.

[0212] ④ Calculate and record the coulombic efficiency at different discharge rates after 100 cycles: Coulombic efficiency = (discharge capacity / charge capacity) × 100%. The results are shown in Table 1.

[0213] Table 1

[0214] As can be seen from Table 1, when the electronegativity of the dopant atoms in the doped graphene is ≥ 2, the corresponding battery can achieve higher rate performance. Furthermore, from Examples 1, 3, 4, 9, and 10, it can be seen that when the mass percentage of the dopant atoms in the doped graphene oxide is 1% to 15%, the battery can exhibit better rate performance.

[0215] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0216] The above-described embodiments merely represent several implementation methods of the present application. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art could make various modifications and improvements without departing from the spirit of the present application, all of which fall within the scope of protection of the present application. Therefore, the scope of protection of the present patent application shall be determined by the appended claims.

Claims

1. A separation film, It is characterized in that It comprises a first isolation film substrate and a modified layer located on the surface of the first isolation film substrate, wherein the modified layer contains doped graphene oxide, and the electronegativity of the doped atoms in the doped graphene oxide is ≥2.

2. The isolation film according to claim 1, It is characterized in that The doped graphene oxide satisfies at least one of the following characteristics (1) to (3): (1) The mass percentage of the doping atoms in the doped graphene oxide is 1% to 15%; (2) the doping atoms include at least one of F atoms, N atoms, S atoms and B atoms; (3) the doped graphene oxide comprises at least one of granular doped graphene oxide and flake doped graphene oxide; Optionally, the Dv50 of the granular doped graphene oxide is 0.5 μm to 5 μm; Optionally, the thickness of the flake-shaped doped graphene oxide is 0.5 nm to 3 nm, and the flake diameter is 0.2 μm to 10 μm.

3. The isolation film according to claim 1 or 2, It is characterized in that The modified layer satisfies at least one of the following characteristics (1) to (2): (1) The porosity of the modified layer is 5% to 30%; (2) The thickness of the modified layer is 2 μm to 5 μm.

4. The separator according to any one of claims 1 to 3, It is characterized in that The first isolation film substrate satisfies at least one of the following characteristics (1) to (3): (1) The material of the first isolation film substrate includes a polymer material; Optionally, the polymer material includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride and polyvinyl chloride; Further optionally, the weight average molecular weight of the polymer material is 100,000 to 1,000,000; (2) the porosity of the first isolation film substrate is 40% to 80%; (3) The thickness of the first isolation film substrate is 3 μm to 30 μm; Optionally, the first isolation film substrate has a thickness of 5 μm to 25 μm.

5. The separator according to any one of claims 1 to 4, It is characterized in that The invention also includes a second isolation film substrate, wherein the second isolation film substrate is located on a surface of the modification layer away from the first isolation film substrate.

6. The isolation film according to claim 5, It is characterized in that The second isolation film substrate satisfies at least one of the following characteristics (1) to (3): (1) The material of the second isolation film substrate includes a polymer material; Optionally, the polymer material includes at least one of polypropylene, polyethylene, polyamide, polyester, polytetrafluoroethylene, polyvinylidene fluoride and polyvinyl chloride; Further optionally, the weight average molecular weight of the polymer material is 100,000 to 1,000,000; (2) the porosity of the second isolation film substrate is 40% to 80%; (3) The thickness of the second isolation film substrate is 3 μm to 30 μm; Optionally, the second isolation film substrate has a thickness of 5 μm to 25 μm.

7. The separator according to any one of claims 1 to 6, It is characterized in that The modified layer also contains a binder; Optionally, the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyvinylidene fluoride; Optionally, the mass ratio of the binder to the doped graphene oxide is (0.01-0.05):

1.

8. The separator according to any one of claims 1 to 7, It is characterized in that The modified layer also contains a dispersant; Optionally, the dispersant includes at least one of polyethyleneimine and its derivatives, hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer and polyethylene glycol; Optionally, the mass ratio of the dispersant to the doped graphene oxide is (0.01-0.08):

1.

9. The separator according to any one of claims 1 to 8, It is characterized in that The modified layer also contains a thickener; Optionally, the thickener includes at least one of sodium hydroxymethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropyl methylcellulose, polyacrylate, polyurethane and polyether; Optionally, the mass ratio of the thickener to the doped graphene oxide is (0.005-0.05):

1.

10. A method for preparing an isolation film, It is characterized in that The steps include: A slurry including doped graphene oxide is applied to a surface of a first isolation film substrate and cured to form a modified layer including the graphene oxide on a corresponding surface of the first isolation film substrate, wherein the electronegativity of doped atoms in the doped graphene oxide is ≥2.

11. The method for preparing the isolation film according to claim 10, It is characterized in that After applying the slurry including doped graphene oxide to the surface of the first isolation film substrate, before curing, the following steps are also included: The second isolation film substrate is covered on the surface of the slurry.

12. The method for preparing a separator according to any one of claims 10 to 11, It is characterized in that The curing includes heat pressing and drying in sequence.

13. The method for preparing the isolation membrane according to claim 12, It is characterized in that The hot pressing satisfies at least one of the following characteristics (1) to (3): (1) The temperature of the hot pressing is 120° C. to 150° C.; (2) The hot pressing pressure is 3 MPa to 8 MPa; (3) The hot pressing time is 1 min to 5 min.

14. The method for preparing a separator according to any one of claims 12 to 13, It is characterized in that The drying satisfies at least one of the following characteristics (1) to (3): (1) The drying temperature is 90°C to 120°C; (2) The drying time is 6 hours to 12 hours; (3) The drying is carried out under vacuum conditions.

15. A battery, It is characterized in that An isolation film comprising the isolation film according to any one of claims 1 to 9 or an isolation film prepared by the method for preparing the isolation film according to any one of claims 10 to 14.

16. An electrical device, It is characterized in that Comprising the battery of claim 15.